Individual and Contextual Factors of Radicalisation - Tinnes, Judith (Perspectives on terrorism, 2023)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on individual and contextual factors of radicalisation to terrorism and violent extremism. It focuses on recent publications (up to November 2023) and should not be considered as exhaustive. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text and reference retrieval systems have been employed to broaden the search.